PENGARUH PENAMBAHAN TEPUNG RUMPUT LAUT Eucheuma cottonii PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) - Regina Burhani; Nanda Diniarti; Dewi Putri Lestari (Journal of Fish Nutrition, 2022)
Tilapia is one of the types of freshwater fish that have a high economic value. One of the problems in cultivation activities is the price of raw materials feed that is relatively expensive. To overcome this, the use of seaweed meal can be one of the alternative ingredients in reducing the use of fish flour and soy flour in feed. The purpose of this study was to analyze the effect of the addition of E. cottonii seaweed meal on feed on the growth and survival of tilapia (O. niloticus). The research method used is an experimental method using a complete randomized design (RAL), with 4 treatments and 3 repeats. The treatment in this study was P1 (control / no seaweed meal), P2 (E. cottonii meal 4%), P3 (E. cottonii meal 8%), P4 (E. cottonii meal 12%). Data is analyzed using diversity fingerprint analysis (ANOVA) with a 95% confidence level. The results showed that the addition of E. cottonii seaweed meal to feed had a significant effect on absolute weight growth and absolute long growth in tilapia, but did not have a significant effect on specific growth rates, efficiency of feed utilization, feed conversion rate and tilapia survival.